Books and ideas after Seth Siegelaub - Pichler, Michalis 1980-; Siegelaub, Seth 1941-2013 (Sternberg Press, 2016)
Books and Ideas after Seth Siegelaub spans an arc of tension between the works of Seth Siegelaub and contemporary cultural production. It features an interview with Seth Siegelaub, two essays by Regine Ehleiter and Michalis Pichler, and an extensively illustrated catalogue with bibliographic details. In preparation for the project, Siegelaub and Pichler met twice in Amsterdam, where they had a long recorded conversation about books, living with books, being intimately connected with books, and producing books, and about the recent emergence of contemporary publications that show clear reference to books Siegelaub had produced, both piracies and homages, and not always to his delight. Books by Siegelaub that are often paraphrased include the Xerox Book (1968), which was printed in offset and has since been xeroxed by various artists and publishers in many different ways, the catalogue exhibitions from 1969, as well as Lawrence Weiner’s Statements (1968). These publications are often taken as starting points for new projects, which are derivative and yet substantial artworks in their own right. Also, Siegelaub’s engagement with the Art Workers’ Coalition and subsequent draft of The Artist’s Reserved Rights Transfer and Sale Agreement has had wide reception and reaction in contemporary art and activism.
Keywords: Siegelaub, Seth -- 1941-2013; Rezeption